2009
DOI: 10.1056/nejmoa0808455
|View full text |Cite
|
Sign up to set email alerts
|

Antivenom for Critically Ill Children with Neurotoxicity from Scorpion Stings

Abstract: Among critically ill children with neurotoxic effects of scorpion envenomation, intravenous administration of scorpion-specific F(ab')(2) antivenom resolved the clinical syndrome within 4 hours, reduced the need for concomitant sedation with midazolam, and reduced the levels of circulating unbound venom. (ClinicalTrials.gov number, NCT00685230.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(91 citation statements)
references
References 14 publications
1
82
0
8
Order By: Relevance
“…Similarly, studies on children stung by Centruroides in Arizona have reported signifi cant improvement in the neurological picture, as well as a reduction of circulating venom compared to placebo (21) .…”
Section: Treatmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, studies on children stung by Centruroides in Arizona have reported signifi cant improvement in the neurological picture, as well as a reduction of circulating venom compared to placebo (21) .…”
Section: Treatmentmentioning
confidence: 90%
“…Majority of the species of the Buthidae family induce similar reactions, except for Tityus obscurus in Brazil (18) (19) (20) , Centruroides (21) , and Parabuthus (22) , which also induce neurological manifestations. Signs and symptoms reported in envenoming caused by T. obscurus in some regions of Pará (Santarém) involve myoclonus (a sensation of an electric shock throughout the body), dysmetria, dysarthria, ataxia, paresthesias and hyperrefl exia, compatible with acute cerebellar syndrome with abnormal muscle movements, in addition to rhabdomyolysis and acute renal failure (19) (20) .…”
Section: Systemicmentioning
confidence: 99%
“…Çocuklar-da akrep zehirlenmeleri erişkinlere göre daha ağır seyretmektedir. Antivenom karşıtı yayınlar olmasına rağmen ilk 1-4 saatte antivenom tedavisi ile kardiyak-sistemik bulguların önlenebildiğini gösteren yayınlarda vardır (21)(22)(23)(24)(25). Hastada antivenom tedavisine rağmen sistemik bulgular devam ediyor ise ilk tedaviden 1 saat sonra 2. doz antivenom tedavisi verilebilir (11).…”
Section: Bulgularunclassified
“…Subsequent one-vial doses are recommended if symptoms do not resolve after a 30-60-min observation period [4]. A randomized, double-blinded placebo-controlled trial of 15 patients showed complete resolution of all 8 patients who received the antivenom within 4 h of administration versus 1 of 7 patients who received placebo [5]. Anascorp® use has been shown to be safe and effective and has allowed affected patients to be discharged from the emergency department with resolution of symptoms [6].…”
Section: Introductionmentioning
confidence: 99%